The Impact of Patient Demographics on Nurse-Patient Relationships in Healthcare Settings: Analyzing the Role of Age, Marital Status, and Educational Level - Shrestha, Rabina; Bohara, Kapil (NPRC Journal of Multidisciplinary Research, 2024)
Patient's satisfaction is the main objective of any healthcare organization. Patients are the regular customers of healthcare organizations not once so we should satisfy them by fulfilling need wants and demand. As a single satisfied customer brings thousands of other customers and patients are our customers. Patient satisfaction plays a vital role in healthcare organization and medical research. Patient satisfaction is required to build trust in patients. As trust of patients towards hospital and healthcare providers depends on patient satisfaction. For this research, we took trust and how it affects nurse-patient relationship is the main theme of study. A nurse is a skilled healthcare professional who plays a vital role in caring for people who are sick, injured, or unable to care for themselves. A good nurse-patient relationship is required for proper treatment of the patient and care. The main purpose of this study is to investigate nurse-patient relationship in healthcare settings. Through this research we focused whether the nurse-patient relationship differs with the age, marital status, occupation, and education level of the patient. For this study, hypothesis was developed to investigate the nurse-patient relationship. A quantitative research strategy was adopted, and convenience sampling techniques were used to collect data from the patients. This study shows the nurse-patient relationship in healthcare settings.